ANALISIS PREFERENSI KONSUMEN KEDAI KOPI DI KOTA CIREBON - Poetro, Adlan Gustav Alviano; Noor, Trisna Insan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The development and growth of coffee shops has become very rapid, espescially in the city of Cirebon with different characteristics and with various consumer preferences. This study aims to determine the characteristics of coffee shop consumer in Cirebon City and to analyze consumer preferences for coffee shops in Cirebon City. This study used a survey method involving 100 respondents using analytical tools, namely Conjoint Analysis. In this study, there are 6 attributes used and there are sub attributes in it. The research location was chosen deliberately by taking 5 coffee shops located in 5 sub-districts of Cirebon City, namely Coffee Lieur, Kopi Roemah Kesambi, Sans Coffee, Umah Rindjani, and Kopi Nama. The results of this study indicate that customer preferences for coffee shops in Cirebon City have quite complete facilites, cool and quiet atmosphere, varied products, responsive service, easy to reach, and price in the range of IDR 15.000 – IDR 30.000.